1999
DOI: 10.1207/s15328023top2602_16
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Mediated Group Projects: Facilitating Collaborative Learning with the World Wide Web

Abstract: We present the use of the World Wide Web (Web) to facilitate collaborative group work in 2 teaching environments: high school and graduate school. In the first case, high school students (N = 19) participating in a university minicourse worked in small groups for 25 hr conducting research and preparing a report on the Web. In the second case, psychology graduate students (N = 8) used personal Web sites for their seminar work. We found that the Web environment facilitated group work by providing (a) clear demar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Cooperative learning is regarded as an important element of active teaching (Bryant 1978;Psychl, Clark, and Abarbanel 1999) and small-group cooperative work during teaching sessions has been recommended in the context of large-class teaching at college level. According to Cooper and Robinson (2000), small-group work can contribute to effective teaching and learning by promoting cognitive elaboration, enhancing critical thinking, providing feedback, promoting social and emotional development, appreciating diversity and reducing student attrition.…”
Section: Active Teaching and Learning In Large College And Universitymentioning
confidence: 99%
“…Cooperative learning is regarded as an important element of active teaching (Bryant 1978;Psychl, Clark, and Abarbanel 1999) and small-group cooperative work during teaching sessions has been recommended in the context of large-class teaching at college level. According to Cooper and Robinson (2000), small-group work can contribute to effective teaching and learning by promoting cognitive elaboration, enhancing critical thinking, providing feedback, promoting social and emotional development, appreciating diversity and reducing student attrition.…”
Section: Active Teaching and Learning In Large College And Universitymentioning
confidence: 99%
“…However, as highlighted in other studies the use of Internet for educational web activities has identified a number of benefits in using it for instruction such as convenience, speed of communication, quick and remote access to information, instant feedback, and cost saving [11,12,13].…”
Section: Methodsmentioning
confidence: 98%
“…A second self-report questionnaire evaluating the usefulness ofthe Internet in career counseling was used to answer the second research question and is also included in the Appendix. The seven questions in this section were developed after reviewing several surveys assessing the use of the Internet as an instructional tool (Pychyl, Clarke, & Abarbanel, 1999;Warnke, 1996). Both the graduate student counselors-in-training and their volunteer clients were asked to evaluate their experience using the Internet by responding to 7 evaluative statements using a 6-point scale (0 = strongly disagree, 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%